(untitled) (Physical Education, Health and Social Sciences, 2025)
Cholelithiasis is a significant public health concern, prevalent in affluent regions. It affects adults more than children or the elderly, with higher rates in women. Limited epidemiological research on gallstones in men, traditionally seen as a female-related disorder. To find the frequency and common symptoms of cholelithiasis in adults. A descriptive cross sectional study was conducted. The sample of 141 patients was collected through services hospital, Lahore via purposive sampling. Data was collected through the questionnaire based on demographic and common symptoms related to cholelithiasis. Then, collected data was analyzed using SPSS v26. The percentage of 32% male and 68% female were present in 141 selected patients. The age distribution have shown that 67% of patients ranges between 25-35 years while 33% lie between 36-50 years. Marital status showed 41% single and 59% married patients. Cholelithiasis frequency has depicted the 100 diagnosed patients diagnosed, and 41 patients non diagnosed. Common symptoms included right hypochondrium pain (92%), pain backward to the region (77%), fever (74%), and jaundice (52%). Vomiting was prevalent in 90% of patients. Fatty food association with pain was reported to be 85%. Bloating and dyspepsia were seen in 76% and 85% of patients, respectively. Pain in right shoulder was present in 74% and heartburn in 84% of patients. The study reported the high prevalence of cholelithiasis in the population especially females. Common symptoms include right hypochondria pain radiating to the back, vomiting, nausea, fever, dyspepsia, pain between shoulder blades and in the right shoulder, bloating, and heartburn.